Sports Injury and Illness Epidemiology: Great Britain Olympic Team (TeamGB) surveillance during the Sochi 2014 Winter Olympic Games - Palmer-Green, D.; Elliott, N. (British Journal of Sports Medicine, 2015)
Background: Sports injury and illness surveillance is the first step in injury and illness prevention, and is important for the protection of both athlete health and performance in major competitions.